The neuroprotective effect of curcumin against ATO triggered neurotoxicity through Nrf2 and NF-κB signaling pathway in the brain of ducks - Shaofeng Wu (Elsevier, 2021)
Arsenic trioxide (ATO) has confirmed as a global pollutant, the toxic effect of which was not fully understood and lack effective therapies to against its associated toxicities. Curcumin (Cur) is a beneficial natural pigment for its antioxidant and anti-inflammatory properties. The purpose of this paper was to illustrate the antagonism of Cur against ATO-induced neurotoxicity. A total of 40 ducks were divided randomly into 4 groups and conducted via bite and sup for 28 days: control group (Control); 2 mg/kg ATO group (Low ATO); 4 mg/kg ATO group (Middle ATO); 8 mg/kg ATO group (High ATO); 400 mg/kg Cur group + 8 mg/kg ATO (Cur+ATO). The results showed that ATO exposure can hinder the duck growth and arsenic element accumulation rate increased in a dose-dependent manner. We observed neuronal shrinkage and vacuolize of HE staining in the ATO-treated group. In addition, SOD activity and T-AOC level reduced while MDA content increased in the ATO-exposed group. ATO exposure can decrease the expression of anti-oxidation related mRNA and proteins (Nrf2, SOD-1, GPX-1, CAT, Trx and HO-1) and anti-inflammatory makers (IL-4, IL-10), increased the expression of Keap1, NF-κB and pro-inflammatory makers (TNF-α, IL-1β, IL-18, IL-2, IL-6, INOS and COX-2). ATO treated might cause blood-brain barrier (BBB) damage through degradation of the tight junction proteins (TJs) occludin and ZO-1. Importantly, the experimental results also showed that Cur can alleviate oxidative stress, inflammatory response and BBB injury caused by ATO exposure through Nrf2 and NF-κB signaling pathway. The results suggested Cur exerted as a food additive and provided novel potential benefits of ATO toxicology in inflammation of the brain.